PHYSICOCHEMICAL CHANGES DURING STORAGE OF ULTRA HIGH TEMPRATURE PROCESSED WHOLE AND SKIMMED BUFFALO MILK (Biological Sciences - PJSIR, 2002)
Physicochemical changes in Ultra high temperature  (UHT) whole  and  skimmed  buffalo  milk  stored  at  10, 20  and 40°C for three months were studied. A significant decrease in pH and an increase in titratable acidity occurred during storage of  UHT whole and skimmed milk at 20 and 40°C after three months of storage. At 10°C, viscosity of milk increased to some extent whereas decrease in vicosity was observed at higher temperaures . After three months storage at 40°C, total ash and lactose contents decreased by 18.5% and 6.67% from UHT  whole  milk  and  20.93%  and  15.66%  from  UHT  skimmed milk, respectively . Similarly, decrease in casein nitrogen was 14.58% and 16.66% for lJHT whole and skimmed milk respectively , after three months storage at 40°C. On the other hand, non protei n nitrogen  and  non  casein  nitrogen  increased by 68.72% and 47 .72% i n UHT whole milk and 64.28% and 31.25% in UHT skimmed m ilk , respecti vely. However total nitrogen content of UH.T milk remained  unchanged  during  storage.  A  significant i ncrease i n  hydroxy methyl furfural (HMF) values was observed depending upon the initial concentration of lactose in both types of milk and storage conditions . These changes were also observed during storage of UHT milk at 10 and 20°C but to a lesser extent. Subjective evaluation studies showed that UHT milk stored at 10 and 20°C was organoleptically acceptable  after  three  months storage. On the other hand , sensory quality characteristics were adversely  affected  at  40°C  after  three  months storag  of UHT  whole  and  skimmed  milk